2021
DOI: 10.1186/s12992-021-00693-5
|View full text |Cite
|
Sign up to set email alerts
|

Study problems and depressive symptoms in adolescents during the COVID-19 outbreak: poor parent-child relationship as a vulnerability

Abstract: Background Little is known about the prevalence of and risk factors for adolescent mental health problems during the COVID-19 outbreak. We aimed to investigate the prevalence of depressive symptoms, their association with study-relevant problems, and the moderating effect of parent-child relationship among Chinese adolescents during the school closures. Methods We performed a cross-sectional analysis with data collected in middle and high schools i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Parents had to manage multiple tasks and spend much more time with their children, thus increasing the risk of conflict between them. A study conducted in Taizhou reported that when students had study problems due to school closures, those with poor parent–child relationship were particularly vulnerable to depressive symptoms ( Wang et al, 2021 ). On the contrary, harmonious parent–child relationship, especially parental supportive behaviors and responsive parenting, tend to alleviate the effects of stressors on children’s mental health and promote their prosocial behavior ( Eisenberg et al, 2019 ; Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parents had to manage multiple tasks and spend much more time with their children, thus increasing the risk of conflict between them. A study conducted in Taizhou reported that when students had study problems due to school closures, those with poor parent–child relationship were particularly vulnerable to depressive symptoms ( Wang et al, 2021 ). On the contrary, harmonious parent–child relationship, especially parental supportive behaviors and responsive parenting, tend to alleviate the effects of stressors on children’s mental health and promote their prosocial behavior ( Eisenberg et al, 2019 ; Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that Moroccan high school students (males and females) reported more symptoms coupled to depression and paranoid ideation during the COVID-19 pandemic compared with the before-COVID-19 period. This increase in depression symptoms reported by students from the 2020 sample could be associated with a higher likelihood of perceiving deteriorations induced by the COVID-19 pandemic in different areas of daily life, including conflict with family members; loneliness; and worry about their studies, relationships with peers, and health (20,(77)(78)(79)(80)(81). Indeed, Magson et al (77) found that increased conflict with fathers was associated with more depressive symptoms; this conflict may reflect a developmental gap in the inherent desire of adolescents to connect with their peers and seek greater autonomy from their parents (82).…”
Section: Comparison Of the Mental Health Profile Of Moroccan Adolesce...mentioning
confidence: 95%
“…Although the education sector had launched online education to minimize the learning loss, there were still a substantial proportion of students who were not satisfied with online education and were not participating effectively, especially those from families or regions with lower socioeconomic status (Ma et al, 2021). The problems related to studies, such as having difficulty in studying at home and dislike of remote learning, have been reported to be prevalent among adolescents during the closure of schools, and they were associated with more severe depressive symptoms (Wang et al, 2021). Among hospitals that provide mental health services to children and adolescents in China, 9% closed their outpatient units and 25% closed inpatient wards during the COVID-19 outbreak (Cui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%